Fly ash: An alternative to powdered activated carbon for the removal of eosin dye from aqueous solutions - V.O. Njoku (Bulletin of the Chemical Society of Ethiopia, 2013)
This paper reports the use of powdered activated carbon (PAC) and raw coal fly ash (RFA) in the removal of eosin dye from aqueous solution in batch processes. Operational parameters such as contact time, initial dye concentration, pH and temperature were investigated. Adsorption equilibrium was established in 120 min for the two adsorbents. Langmuir and Freundlich isotherms were used to fit the adsorption data. Langmuir model gave the best fit in both cases. The adsorption capacities of PAC and RFA were found to be 62.28 mg/g and 43.48 mg/g, respectively. The highest percentage of eosin dye removal for both PAC (98%) and RFA (90%) was observed at pH 2. Pseudo first-order and pseudo second-order kinetic models were used to fit the adsorption data. Pseudo second-order kinetic model gave the best description of the adsorption of eosin dye onto the two adsorbents. Thermodynamic parameters, ΔH0, ΔS0 and ΔG0 confirmed the physical nature, spontaneity and the endothermic nature of the adsorption process. A regeneration technique and a process calculation for evaluating the adsorbent dose required were carried out. This study has shown that RFA is a good alternative adsorbent in the removal of eosin dye from aqueous solution.